Qal’e Nehbandan: Evidence of the Parthian Period in Eastern Iran - Dana, Mohsen; Nasrabadi, Alireza; Sharifan, Hadi (Anabasis. Studia Classica et Orientalia, 2019)
The site of Qal’e Nehbandan appears to be a Parthian foundation. It can be identified with the ancient town of Neh, mentioned by Isidoros of Charax. Neh was a small desert town that played an important role at ancient routes connecting the Great Khorasan road in the north (via North Khorasan, Margiana and Bactria) with the Indian road (via Sistan to the Indus valley) in the south.